Beta‐lactam hypersensitivity in children: Frequency and risk factors. Issue 1 (9th December 2020) - Ben Romdhane, Haifa; Ben Fredj, Nadia; Ben Fadhel, Najah; Chadli, Zohra; Abderrahmen, Ahlem; Boughattas, Naceur A.; Chaabane, Amel; Aouam, Karim
Abstract : Aims: To determine the frequency of an authentic β‐lactam (BL) hypersensitivity (HS) amongst a large number of children and to identify clinical risk factors that predict this hypersensitivity. Methods: All children with suspected BL allergy were evaluated by skin tests (ST) with the suspected BL. A 1‐day oral provocation test (OPT) was performed in children with negative ST. We defined an authentic BL‐HS case if the child exhibited a positive ST or a positive OPT. Risk factors associated with BL‐HS were assessed using a univariate analysis. Covariates showing a P ‐value <.2 were included in the multivariate logistic regression analysis to determine independent predictors. Results: A total of 354 patients reporting 368 suspected BL reactions were included. The diagnosis of BL‐HS was established in 24 children (6.7%). All these children had a positive ST. OPT was performed in 30 patients and was negative in all of them. In 110 children with a negative ST, BL was tolerated. In the risk factors analysis, 164 children were included. Older age (>5 years) at the reaction (odds ratio = 1.11; 95% confidence interval, 1.01–1.22; P = .02) and BL administered (odds ratio = 7.7; 95% confidence interval, 2.76–21.8; P < .001) were significantly associated with authentic BL‐HS. Conclusion: BL‐HS should be evaluated with an appropriate allergy work‐up before strict prohibition is made. In addition, age of patient and BL involved can be used as predictive factors of developing BL‐HS in this population.